The reality and fundamentals of the poultry industry and its implications on the prices of eggs and chickens in Iraq for the period from 2000 to 2009 (analytical study) - محمد علي سلام نعمة (Journal of Economics and Administrative Sciences, 2011)
Despite all the possibilities held by Iraq for the production of poultry , but there is low and clear in the level of production and a rise in costs and a decline in per capita consumption is due to a number of reasons, including poor investment , stop government subsides , dumping policies , market Bolmottagat imported , the contribution of the merchant squandering of national capacity , weak base material for the growth of this sector , the security situation and the crisis of energy and others . Despite all this research has shown that there are great investment opportunities in this very sector of the market size and absorptive capacity of his and the growth of per capita income and level of culture preference for local product to foreign , through the promotion of investment types and input subsides and opening new marketing and others